Substitution of Cratylia argentea and Erythrina poepiggiana by square banana in Silages. - Montero-Durán, Eduardo (2021)
The objective of this research was to evaluate the effect of the addition of Square banana on the nutritional and fermentative quality of silages of Cratylia argentea and Erythrina poepiggiana. The study was carried out in Upala, Costa Rica from April to November 2016. A completely randomized factorial design was used with 4 levels of Square banana and 2 species of legumes. Silages were made in 5 kg plastic bags and stored during 50 days. At the opening, bromatological characteristics of silages were measured, as well as the fermentation indicators. It was detected that the Square banana affects fermentation with pH values ranging from 4.3-4.8 and lactate 1.61-3.91% DM. In the same way, the Square banana affects the nutritional value, with concentrations of crude protein, non-fibrous carbohydrates and neutral detergent fiber that ranged between 9.40-16.66, 21.78-57.88 and 21.15-48.55% of DM, respectively. The energy content increased as the amount of Square banana did in the mixture, the energy of the silage fluctuated between 1.38-1.73 Mcal/kg DM. In conclusion, all the silages with Square banana presented adequate characteristics to be used as a ruminant supplement, although the best results were obtained at 15% and 30% levels.